Effects of rhythmic-based exercise program in children - Bogdan Tomić; Slobodan Balać; Angela Mesaroš Živkov (Exercise and Quality of Life)
Physical fitness (PF) is an exceptional indicator of health in childhood and prevents chronic conditions in adulthood. Various exercise modalities have been studied for their impact on children's PF, but rhythmic-based exercises have received less attention. Hence, we structured the rhythmic-based exercise program to provide an approach to developing children's PF over ten months. The non-randomized pre-post-controlled 2x2 design included 154 children (REG, rhythmic-based exercise group, n=75, CG, control group, n=79). We assessed PF performance using the modified 20 m shuttle run test, the standing long jump, the 30-second sit-up test, and the sit-and-reach test before and after 10 months of rhythmic-based exercise program. The 2x2 mixed ANCOVA showed that all PF test performances improved significantly more in REG than in CG from a small (Standing long jump for 3%), across medium (Sit-ups for the 30s for 12%), to a large extent (Modified 20 m shuttle run test for 14% and Sit and reach for 23.1%). The rhythmic-based exercise program provoked extensive flexibility and overall muscular and cardiorespiratory fitness developments. Further randomized controlled trials should be conducted to support or contrast our results.